3D sensors implementation for mobile robots and autonomous vehicles navigation - Valverde Moreno, Sergio (2020)
Autonomous vehicles navigation, as well as mapping areas have endless commercial andindustrial applications. This article explains the development of an application that allows amobile robot to navigate autonomously, avoiding obstacles, until it reaches a specific coordinatepoint defined by the user, using low cost 3D sensors. For the design and implementation of thisapplication, it is necessary to keep in mind that navigation and obstacle detection are based onthe use of 3D sensors. For this purpose, the Kinect was selected. The simulation and testing ofthe project was done in a special simulation environment for robotic applications, called V-REP.The navigation algorithm for obstacle avoidance was implemented through the potential fieldstheory. Other sensors, as GPS and IMU, were used to determine the robot’s spatial position andorientation, with the objective of defining a trajectory to the goal coordinate point, thus doing amore efficient navigation. Finally, real data from the physical sensors was used to corroboratethe functioning of the application, with the purpose of comparing it with the previously obtainedresults from the simulated part.